1986
DOI: 10.1126/science.2425431
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Antigenic Determinants of Some Clinically Important Insect Allergens: Chironomid Hemoglobins

Abstract: Determination of the molecular structure and properties of allergens that elicit severe immediate-type hypersensitivity diseases in humans and a knowledge of the structure of their antibody-binding sites should provide new insight into the pathogenetic mechanisms of allergic diseases. Monomeric and homodimeric hemoglobins (CTT I to X) have been identified as potent allergenic components of Chironomidae, a family of Diptera. Immunologic investigations of peptides of three of these hemoglobins (CTT IV, CTT VI, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…A similar high antigenic character of globins is observed for the Hbs/Mbs of the nematodes where the pigment is found in the excretory/ secretory products of Trichostrongylus colubriformis and Nippostrongylus brasiliensis (18 -20). The extracellular Hbs of Ascaris suum and Chironomus thummi thummi are also documented as potent allergens (21,22). The purpose of the high antigenic character of the Hbs/Mbs of the parasite and their occurrence in the excretory/secretory products is unknown.…”
mentioning
confidence: 99%
“…A similar high antigenic character of globins is observed for the Hbs/Mbs of the nematodes where the pigment is found in the excretory/ secretory products of Trichostrongylus colubriformis and Nippostrongylus brasiliensis (18 -20). The extracellular Hbs of Ascaris suum and Chironomus thummi thummi are also documented as potent allergens (21,22). The purpose of the high antigenic character of the Hbs/Mbs of the parasite and their occurrence in the excretory/secretory products is unknown.…”
mentioning
confidence: 99%
“…Various algorithms of epitope prediction exist but they are mostly not better than random. However, the N terminus of the insect allergen Chi t 1.01 (hemoglobin component of Chironomus thummi [1]) was predicted to contain B and T cell epitopes [2, 3]. These predictions could be confirmed experimentally.…”
Section: Introductionmentioning
confidence: 48%
“…Preliminary structural data on a few allergens based on modeling studies have been published (18,19); NMR solution structures have been reported for two allergens from ragweed (20,21), but this is the first report concerning the crystallization of a grass pollen allergen. Such studies are possible due to the availability of recombinant allergens in sufficient amounts, and our experience leads us to suggest that crystallographic techniques may make a substantial contribution to allergy research.…”
Section: Discussionmentioning
confidence: 99%